2017
DOI: 10.1177/0022487117709742
|View full text |Cite
|
Sign up to set email alerts
|

“It’s 1000 Degrees in Here When I Teach”: Providing Preservice Teachers With an Extended Opportunity to Approximate Ambitious Instruction

Abstract: Teacher educators have a challenging task of designing opportunities for preservice teachers (PSTs) to learn ambitious science teaching (AST). However, with limited time in methods courses and the complexities of AST, opportunities for PSTs to “try out” ambitious instruction are difficult to construct and analyze. To address this problem, we describe our enactment of a type of extended pedagogical rehearsal that we call “macroteaching” in a secondary science methods course. Framed as a design experiment, we co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 38 publications
0
27
0
Order By: Relevance
“…Other instances of "huddles" taking place between teachers have also indicated that this is productive form of joint work shared between teachers. For example, Stroupe and Gotwals (2018) detail how PSTs used "time outs" as a chance to work through a dilemma of teaching and learning as a sidebar to the busy work of carrying out highly interactive science teaching with multiple groups of students. Kazemi, et al (2016) describe how this pause in the action to talk through pedagogical pathways and interpretations of student thinking can take the form of a teacher educator intervening in a PST's teaching or it can take the form of a joint deliberation where all participants contribute to the discussion during a "time out" from teaching.…”
Section: This Finding Echoes Whatmentioning
confidence: 99%
“…Other instances of "huddles" taking place between teachers have also indicated that this is productive form of joint work shared between teachers. For example, Stroupe and Gotwals (2018) detail how PSTs used "time outs" as a chance to work through a dilemma of teaching and learning as a sidebar to the busy work of carrying out highly interactive science teaching with multiple groups of students. Kazemi, et al (2016) describe how this pause in the action to talk through pedagogical pathways and interpretations of student thinking can take the form of a teacher educator intervening in a PST's teaching or it can take the form of a joint deliberation where all participants contribute to the discussion during a "time out" from teaching.…”
Section: This Finding Echoes Whatmentioning
confidence: 99%
“…Subsequently, analyses were conducted within the research team, assessing the need for refinements based on the researchers' sense of progress, which was partially informed by the data collected from the PSTs, such as interviews and video recordings of the enactments. In contrast, the iteration cycle in the study by Stroupe and Gotwals (2018) was less systematic. Rather than simply prescribing learning opportunities for the PSTs to enact, the researchers introduced the concept of macroteaching as an overall framework, in which learning opportunities emerged 'as the instructors and PSTs made sense of pedagogical moments' (Stroupe & Gotwals, 2018, p. 300).…”
Section: 1mentioning
confidence: 87%
“…based on the data collected from previous cohorts. Other studies describe the iterative cycles in which refinements were implemented regarding a single cohort (e.g., Stroupe & Gotwals, 2018).…”
Section: 1mentioning
confidence: 99%
“…We then attended to the "timescale" or duration of the classroom instruction segment in each core-practice approach described by teacher educators. That is, we attempted to classify from larger scale domains of teaching practice such as a unit (see Stroupe & Gotwals, 2017) to narrower 15-min episodes of teaching (e.g., see Ghousseini, Beasley, & Lord, 2015). Through multiple rounds of discussion and analytic memos, however, we found that timescale did not by itself capture the meaningful differences of a teacher educator's incorporation of core practices.…”
Section: Category Developmentmentioning
confidence: 99%